2021
DOI: 10.1080/00396265.2021.1878338
|View full text |Cite
|
Sign up to set email alerts
|

An attempt to analyse Iterative Data Snooping and L1-norm based on Monte Carlo simulation in the context of leveling networks

Abstract: The goal of this paper is to evaluate the outlier identification performance of iterative Data Snooping (IDS) and L1-norm in leveling networks by considering the redundancy of the network, number and size of the outliers. For this purpose, several Monte-Carlo experiments were conducted into three different leveling networks configurations. In addition, a new way to compare the results of IDS based on Least Squares (LS) residuals and robust estimators such as the L1-norm has also been developed and presented. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The test sample was extended with one characteristic displacement scenario where all network points (PRPs and object points) are undisplaced ) in order to examine the false-positive rate (FPR) of the proposed GREDOD modification, as reported in [ 59 ], where a similar procedure was conducted for outlier analysis. FPR is defined as the number of false-positive rates divided by the total number of experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The test sample was extended with one characteristic displacement scenario where all network points (PRPs and object points) are undisplaced ) in order to examine the false-positive rate (FPR) of the proposed GREDOD modification, as reported in [ 59 ], where a similar procedure was conducted for outlier analysis. FPR is defined as the number of false-positive rates divided by the total number of experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, many works (see, e.g., [9,15,16]) have investigated critical values for normalized residuals in IDS based on MCS control of false positive rate. Motivated by mentioned works, we propose the following procedure for any robust estimator (Figure 2).…”
Section: Critical Values Based On False Positive Ratesmentioning
confidence: 99%
“…In this context, Lehmann [9] showed that the critical values cannot be derived from well-known univariate test distributions (e.g., normal distribution), due to the correlations between residuals. Hence, in order to fully control false positive rates in geodetic networks, critical values for IDS started to be numerically computed by means of Monte Carlo simulation (MCS) (see, e.g., [15,16]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations